PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP PERILAKU KONSUMTIF MAHASISWA - Chelsea Nayla Putri; Rafeyfa Najla Mutia; Pamella Dinda Azzahra; Edward Barito Panimba; Annisa Ayu Syafira (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to determine the effect of the use of digital wallets on student consumptive behavior. The study used a quantitative approach with causal Associative Design and survey methods through the distribution of questionnaires to 50 students. The results showed that the use of digital wallets affect the increase in consumptive behavior, especially in the aspect of impulsive purchases and weak control over spending. ShopeePay is the most dominant platform used (72%), followed by GoPay (52%), DANA (46%), and OVO (12%). The magnitude of the influence of digital wallets on consumptive behavior varies depending on the characteristics of the respondents, the platforms used and the aspects studied. Therefore, this study recommends increasing digital financial literacy for students to be able to take advantage of the convenience of digital wallets without getting stuck in excessive spending habits